Integrating Visualisation and Spatial Reasoning (VSR) with Realistic Mathematics Education (RME) in Junior High School Mathematics: A Study in Southeast Aceh, Indonesia - Nuri Irmayani; Irvan Irvan (JMEA : Journal of Mathematics Education and Application, 2025)
The low levels of students’ critical and creative thinking skills in mathematics remain a major challenge in 21st-century education. One key factor is the limited use of approaches that foster spatial visualization and contextual conceptual understanding. This study aims to examine the effectiveness of integrating the Visualisation and Spatial Reasoning (VSR) approach with Realistic Mathematics Education (RME), supported by digital technology, in improving the critical and creative thinking abilities of junior high school students in Southeast Aceh, Indonesia. The research used a quasi-experimental method with a pretest–posttest control group design. The sample consisted of two eighth-grade classes: the experimental class received VSR–RME-based instruction using digital media (e.g., GeoGebra and spatial animations), while the control class received conventional instruction. The research instruments were essay-type tests on critical and creative mathematical thinking, validated and proven reliable (α = 0.82). Data analysis included independent t-tests and normalized gain calculations. The results showed a significant difference between the groups, with the experimental class achieving a higher normalized gain of 0.68 (moderate–high category) compared to 0.41 (moderate category) in the control class. These findings indicate that the integrated VSR–RME approach is more effective in enhancing students' critical and creative thinking. The integration of visual–spatial reasoning, contextual learning, and digital technology is recommended as an innovative model for fostering higher-order thinking in mathematics education.